The Correlation Between Archetype Personality and Business Success in Small and Medium Enterprises (SMEs) in Java Island - Bimo Wikantiyoso; Benedicta Prihatin Dwi Riyanti; Angela Oktavia Suryani; Sonny Soeharso (AIBPM Publisher, 2024)
Understanding entrepreneurial success involves exploring various factors, including personality traits and their impact on business outcomes. This study explores the relationship between entrepreneurial personality archetypes and business success among SMEs in Indonesia. Using a quantitative approach, data were collected from 500 MSME entrepreneurs via paper-and-pen and online questionnaires. Pearson Correlation analysis revealed significant positive correlations between business success and the Caregiver (r = 0.243), Seeker (r = 0.340), Lover (r = 0.227), Ruler (r = 0.316), Magician (r = 0.290), Sage (r = 0.277), and Jester (r = 0.235) archetypes. In contrast, the Destroyer archetype showed a negative correlation (r = -0.222). These findings suggest that archetypes promoting self-expression and personal growth positively influence entrepreneurial success, while those focusing on efficiency and results may hinder it. The study underscores the value of aligning personality traits with business strategies to improve outcomes and recommends further research on practical applications in entrepreneurial training programs.